Prevalence, Characteristics, Risk Factors, and Impact of Intestinal Parasitic Infections on School Children in Jeddah, Western Saudi Arabia - Marwan A. Bakarman; Moustafa A. Hegazi; Nadeem S. Butt (Journal of Epidemiology and Global Health, 2019)
Intestinal Parasitic Infections (IPIs) are a major public health problem worldwide, especially among children with a need for periodical evaluation of prevalence and risk factors to adopt an appropriate prevention strategy. This cross-sectional prospective study was conducted to identify prevalence, risk factors, characteristics, and impact of IPIs on school children in different regions of Jeddah, Saudi Arabia. Children were recruited from randomly selected schools. Questionnaires were distributed to students and filled by their parents to collect relevant information about sociodemographic, environmental, and hygienic living conditions. Stool samples and anthropometric measurements as indicators of nutritional status were collected from students who agreed to participate in the study. Fecal samples were examined by direct smear and formol-ether concentration method. Out of 581 collected stool samples, only 31 (5.3%) samples were positive for IPIs especially Blastocystis hominis (10 samples) and Giardia lamblia (six samples). The only two significant risk factors associated with IPIs were drinking water from tanks [odds ratio (OR): 3.35, 95% confidence interval (CI): 1.60–6.99, p = 0.001] and washing hands with only water (OR: 2.63, 95% CI: 1.17–5.93, p = 0.03). There was no significant impact of IPIs on growth parameters or level of children’s academic performance.